2021
DOI: 10.1016/j.schres.2020.11.057
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in psychotic symptoms: Repeated cross-sectional surveys of the population in England 2000–14

Abstract: Background:The number of antipsychotic prescriptions dispensed annually in England has increased substantially over the past decade. It is not known whether this is due to changes in prescribing practices, or an increase in the prevalence of psychosis. To our knowledge, no previous studies have investigated temporal trends in prevalence of psychotic symptoms in non-clinical populations. Methods: We used data from the nationally representative Adult Psychiatric Morbidity Surveys 2000, 2007 and 2014 to (1) test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Although detrimental effects of long-term use (⩾ 2 years) of antipsychotics (AP) and antidepressants (AD) have raised critical debates (Maslej et al, 2017; Murray et al, 2016), their long-term prescriptions are continuing to rise (e.g. Mars et al 2017; Shoham, Cooper, Lewis, Bebbington, & McManus, 2021; Yu, Zhang, Zheng, & Yu, 2020). Some of these prescriptions lack an evidence-base altogether (Mangin et al, 2018; Piek, Kollen, van der Meer, Penninx, & Nolen, 2014), but even for conditions that are assumed to benefit from maintenance therapy beyond the acute phase, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Although detrimental effects of long-term use (⩾ 2 years) of antipsychotics (AP) and antidepressants (AD) have raised critical debates (Maslej et al, 2017; Murray et al, 2016), their long-term prescriptions are continuing to rise (e.g. Mars et al 2017; Shoham, Cooper, Lewis, Bebbington, & McManus, 2021; Yu, Zhang, Zheng, & Yu, 2020). Some of these prescriptions lack an evidence-base altogether (Mangin et al, 2018; Piek, Kollen, van der Meer, Penninx, & Nolen, 2014), but even for conditions that are assumed to benefit from maintenance therapy beyond the acute phase, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these specifications, as already described, a contributing factor to the rise in APD use seems to be their increased off-label use for non-psychotic indications, such as dementia, insomnia, obsessive–compulsive disorder, and generalized anxiety disorder ( 119 ). Survey data from England over the period from 2000 to 2014 found that while psychotic symptoms in the population had increased only slightly over this period, prescription of APDs had doubled ( 120 ).…”
Section: Strategies For Minimizing and Managing Tdmentioning
confidence: 99%
“…Other studies have highlighted this discrepancy between prescription rates for antipsychotics and diagnoses of psychosis, noting that rates of antipsychotic prescribing have been rising faster than psychosis incidence. 19 A UK cohort study also found high rates of antipsychotic prescribing to patients without psychosis and concluded that this reflected psychotropic management of conditions such as depression or anxiety, despite national guidelines recommending that antipsychotics are not clinically indicated for such disorders. 20,21 Clinicians in routine practice may be prescribing antipsychotics (often at low dose) to exert a tranquillising effect and control general features of mental health presentations such as agitation, poor sleep and anxiety.…”
Section: Comparison With Previous Literaturementioning
confidence: 99%